Plasma uric acid levels correlate with inflammation and disease severity in Malian children with Plasmodium falciparum malaria. - Tatiana M Lopera-Mesa (PLoS ONE, 2012)
Plasmodium falciparum elicits host inflammatory responses that cause the symptoms and severe manifestations of malaria. One proposed mechanism involves formation of immunostimulatory uric acid (UA) precipitates, which are released from sequestered schizonts into microvessels. Another involves hypoxanthine and xanthine, which accumulate in parasitized red blood cells (RBCs) and may be converted by plasma xanthine oxidase to UA at schizont rupture. These two forms of 'parasite-derived' UA stimulate immune cells to produce inflammatory cytokines in vitro.We measured plasma levels of soluble UA and inflammatory cytokines and chemokines (IL-6, IL-10, sTNFRII, MCP-1, IL-8, TNFα, IP-10, IFNγ, GM-CSF, IL-1β) in 470 Malian children presenting with uncomplicated malaria (UM), non-cerebral severe malaria (NCSM) or cerebral malaria (CM). UA levels were elevated in children with NCSM (median 5.74 mg/dl, 1.21-fold increase, 95% CI 1.09-1.35, n = 23, p = 0.0007) and CM (median 5.69 mg/dl, 1.19-fold increase, 95% CI 0.97-1.41, n = 9, p = 0.0890) compared to those with UM (median 4.60 mg/dl, n = 438). In children with UM, parasite density and plasma creatinine levels correlated with UA levels. These UA levels correlated with the levels of seven cytokines [IL-6 (r = 0.259, p<0.00001), IL-10 (r = 0.242, p<0.00001), sTNFRII (r = 0.221, p<0.00001), MCP-1 (r = 0.220, p<0.00001), IL-8 (r = 0.147, p = 0.002), TNFα (r = 0.132, p = 0.006) and IP-10 (r = 0.120, p = 0.012)]. In 39 children, UA levels were 1.49-fold (95% CI 1.34-1.65; p<0.0001) higher during their malaria episode [geometric mean titer (GMT) 4.67 mg/dl] than when they were previously healthy and aparasitemic (GMT 3.14 mg/dl).Elevated UA levels may contribute to the pathogenesis of P. falciparum malaria by activating immune cells to produce inflammatory cytokines. While this study cannot identify the cause of elevated UA levels, their association with parasite density and creatinine levels suggest that parasite-derived UA and renal function may be involved. Defining pathogenic roles for parasite-derived UA precipitates, which we have not directly studied here, requires further investigation.ClinicalTrials.gov NCT00669084.